Pengelolaan Gugus Sekolah Dasar Sebagai Strategi Untuk Meningkatkan Mutu Sekolah (Studi Situs Di Gugus I Slamet Riyadi UPTD Dikpora Kecamatan Laweyan Kota Surakarta) - Sesotijowati, Peni, Prof. Dr. Bambang Sumardjoko, Dr. Tjipto Subadi, M. Si (2015)
The objectives of the research are to describe: 1) the elementary schools' cluster management as a strategy to improve the schools' quality , covering planning, organizing, actuating, and controlling; and 2) the supporting and inhibiting factors of elementary schools cluster management in facilitating the teachers' and the principals' activities at the elementary schools cluster at Cluster I Slamet Riyadi UPTD Dikpora Kecamatan Laweyan of Surakarta. The type of the research is a qualitative research. The design of the researh is ethnographical design. The research was undertaken at Cluster I Slamet Riyadi UPTD Dikpora Kecamatan Laweyan of Surakarta. The data collecting method is done using observation, in-depth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The research concludes that: 1) the elementary schools' cluster management as a strategy to improve the schools' quality , covering planning, organizing, actuating, and controlling. The cluster's activities cover the activities for principals, teachers, and students. The activities for teachers were grouped into lower and higher classroom teachers. The controlling activities were done by the school supervisor; and 2) the inhibiting factor of the school cluster management in facilitating the teachers and principals activities cover the financial problem and the human resources quality's inequality. The supprting factors of the school cluster management cover the teachers' demand for achievement, leadership factor, and schools' facilities.